Assessment of safety and patency of 7-mm covered metal stents for preoperative biliary drainage in pancreatic cancer: Prospective multicenter study - Ishiwatari, Hirotoshi; Kobayashi, Yousuke; Kawaguchi, Shinya; Iwashita, Takuji; Kaneko, Junichi; Ito, Jun; Ishikawa, Kazuma; Sato, Junya; Niiya, Fumitaka; Endo, Shinya; Satoh, Tatsunori; Uemura, Shinya; Mori, Keita (Endoscopy International Open, 2025)
For preoperative biliary drainage of pancreatic cancer (PC), a 10-mm diameter metal stent (MS) is commonly used; however, the rate of pancreatitis is high. It is hypothesized that smaller-diameter MS may reduce the rate of pancreatitis. Therefore, we conducted a multicenter prospective study to evaluate the efficacy and safety of 7-mm MS.Patients requiring initial biliary drainage for obstructive jaundice caused by PC and scheduled for surgery from six facilities were included. After endoscopic retrograde cholangiography, a 7-mm MS was placed at the site of biliary obstruction. The primary endpoint was the rate of pancreatitis, and the secondary endpoints included early and late adverse events (AEs). The pancreatitis rate was assumed to be 18% and 5% with 10- and 7-mm MS, respectively; with a power of 80% and one-sided significance level of 10%, the planned enrollment was 38 patients. If pancreatitis occurred in no more than three patients, this indicates that the 7-mm MS effectively reduced incidence of pancreatitis.Overall, 38 patients were enrolled, and 35 patients in whom a 7-mm MS was successfully placed were analyzed. All MS were placed after sphincterotomy. Pancreatitis occurred in four patients (11.4%) and no early AEs were observed. Surgery was performed in 24 patients and late AEs included stent occlusion in eight patients (23%) and cholecystitis in four patients (11%).The 7-mm MS did not reduce incidence of pancreatitis among surgical candidates for PC.
Keywords: Pancreatobiliary (ERCP/PTCD); Strictures; ERC topics; Endoscopic ultrasonography; Biliary tract